Controlled silica core removal from SiO2@MgAl core-shell system as a tool to prepare well-oriented and highly active catalysts - Kondratowicz, Tomasz Stanisław; Šlang, Stanislav; Dubnová, Lada; Kikhtyanin, Oleg; Bělina, Petr; Čapek, Libor (Elsevier Science BV, 2022)
This manuscript presents the preparation of well-oriented @MgAl-layered double hydroxides (LDHs). It extends the reported preparation of SiO2@MgAl-LDH core-shell material (Si/(Si + Mg + Al) molar ratio = 0.54, Mg/Al = 2). There is introduced a new method for the gradual and controlled removal of the SiO2 core from SiO2@MgAl-LDH on treatment with a NaOH solution (1 M) for 1, 2, 4, and 6 h Si/(Si + Mg + Al) molar ratio from 0.06 to 0.52, Mg/Al = 2). Subsequent SiO2 leaching led to empty spheres with properties of the crystalline MgAl-LDH phase preserved. It is proved that @MgAl-LDH spheres formed do not collapse and hence, preserve their orig-inal spherical shape and structural properties. The potential of @MgAl-mixed oxides (MOs) obtained by thermal treatment of @MgAl-LDHs in catalysis is also demonstrated. When this material was used for the aldol condensation reaction of furfural with acetone, the best furfural conversion was obtained for @MgAl-MO with a Si/(Si + Mg + Al) molar ratio of 0.11.
kontrolované odstranění jader siliky z SiO2@MgAl "core-shell" systému jako nástroj pro přípravu dobře orientovaných a vysoce aktivních katalyzátorů
Keywords: core-shell structures; layered double hydroxides; MgAl catalysts; Aldol condensation; base catalysis; core-shell struktura; vrstevnaté double hydroxidy; MgAl katalyzátory; aldolová kondenzace